Relationship between preoperative malnutrition, frailty, sarcopenia, body composition, and anthropometry in elderly patients undergoing major pancreatic and biliary surgery - Wang, Lijuan; Li, Pengxue; Hu, Yifu; Cheng, Bo; Ding, Lili; Li, Lei; Song, Jinghai; Wei, Junmin; Xu, Jingyong (Frontiers in Nutrition, 2023)
Objective: To analyze the correlation between preoperative nutritional status, frailty, sarcopenia, body composition, and anthropometry in geriatric inpatients undergoing major pancreatic and biliary surgery. Methods: This is a cross-sectional study of the database from December 2020 to September 2022 in the department of hepatopancreatobiliary surgery, Beijing Hospital. Basal data, anthropometry, and body composition were recorded. NRS 2002, GLIM, FFP 2001, and AWGS 2019 criteria were performed. The incidence, overlap, and correlation of malnutrition, frailty, sarcopenia, and other nutrition-related variables were investigated. Group comparisons were implemented by stratification of age and malignancy. The present study adhered to the STROBE guidelines for cross-sectional study. Results: A total of 140 consecutive cases were included. The prevalence of nutritional risk, malnutrition, frailty, and sarcopenia was 70.0%, 67.1%, 20.7%, and 36.4% respectively. The overlaps of malnutrition with sarcopenia, malnutrition with frailty, and sarcopenia with frailty were 36.4%, 19.3%, and 15.0%. There is a positive correlation between every two of the four diagnostic tools, and all six p-values were below 0.002. Albumin, prealbumin, CC, GS, 6MTW, ASMI, and FFMI showed a significantly negative correlation with the diagnoses of the four tools. Participants with frailty or sarcopenia were significantly more likely to suffer from malnutrition than their control groups with a 5.037 and 3.267 times higher risk respectively (for frailty, 95%CI: 1.715-14.794, p=0.003 and for sarcopenia, 95%CI: 2.151-4.963, p＜0.001). Summarizing from stratification analysis, most body composition and function variables were worsen in the≥70 years group than in the younger group, and malignant patients tended to experience more intake reduction and weight loss than the benign group, which affected the nutrition diagnosis. Conclusion: Elderly inpatients undergoing major pancreatic and biliary surgery possessed high prevalence and overlap rates of malnutrition, frailty, and sarcopenia. Body composition and function deteriorated obviously with aging.